THE THE ANALYSIS OF COOPERATION PRINCIPLES USE ON PODCAST OF DEDDY CORBUZIER AND NADIEM MAKARIM “HAVING COLLEGE IS NOT IMPORTANT - Sri Listiana Izar; Muhammad Muslim Nasution; Julisah Izar; Putri Wahyu Ilahi (JETLi: Journal of English Teaching and Linguistics, 2021)
This research aimed to describe maxims of cooperation principle on podcast of Deddy Corbuzier and Nadiem Makarim with the theme “Having college is not important”. This research used qualitative descriptive method and pragmatics approach by using the maxim of cooperation principle that explained the principle that are often used by humans in interacting with benefits so that speech is more easily understood by the interlocutor, So the conversation is created that accept each other. In the analysis data the researcher explained the data by describing maxim of quantity, quality, relevance and manner on the podcast.  Data source in this research is podcast video of Deddy Corbuzier and Nadiem Makarim that the researcher watched in the Deddy Corbuzier’s you tube podcast with the theme “Having college is not important”.The data are dialogue and the analysis was described descriptively.Data collection technique used in this research by listening and talking technique and note-taking technique while all the conversation between Deddy Corbuzier and Nadiem Makarim are analyzed by using the maxims of cooperation principle. The presenting data by using Data reduction the first stage in this data analysis is data reduction. The goal is to knowing about valid data or not valid and then  presentation the data, In presenting data, the data has been reduced will be described in detail and obviously then connected with The relevant theories that would l answer the problem of research and the last, conclusion, the conclusion is made for answer the problem formulation so that it can obtained information about the working principle same in podcast of Deddy Corbuzier and Nadiem Makarim with the theme “Having college is not important. This research result was found 9 data which were 2 maxims of quantity, the maxim that make speaker convey information based on speaker’s question, 1 maxim of quality, 4 maxim of relevance, the maxim that make speaker convey information must be one line with speaker’s question either yes or no, 2 maxims of manner obtained from the maxim of praise included in maxim of manner, while maxim of politeness and generosity included in maxim of manner were not found.